A criterion to quantify the effect of superheavy vehicles on asphalt pavements based on layers deformation. Issue 12 (15th October 2022) - Pérez-González, Erdrick Leandro; Bilodeau, Jean-Pascal; Doré, Guy
ABSTRACT: The transit of superheavy vehicles on the road network requires a specific authorisation, which results from a critical analysis of the vehicle's effect on the pavement and other road infrastructure. The assessment of the damage caused by these atypical loading conditions is based on the mechanistic-empirical approach to pavement analysis. In practice, two critical behaviours are taken as reference: (1) fatigue failure and (2) structural rutting of the pavement. However, damage assessment is carried out based on partial stresses, making it an incomplete approach to the conditions described by superheavy loads. This article compares different analysis criteria to quantify the damage caused by superheavy trucks and identifies common interest elements. Additionally, a novel approach is used to study the partial contribution of pavement layers to the structure's performance under atypical loading conditions.